(3GdYhGed GdLOjOI aj GdfMhs - (3GdLQLGfj, GdCTYQj, GdTGaYj, CHh HcQ, YHO GdbGgQ Hf YHO GdQMef Hf eMeO, (B471 (3g`s ((3hdj GdbhLhjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfhHYO aEf GdYhGed aj GdfMh Ydi eG Cdag GdTjN YHO GdbGgQ Hf YHO GdQMef GdLQLGfj eGFI YGed hgj JfbSe Edi bSejf daXjI heYfhjI aGddaXjI efgG JfbSe Edi bSejf SeGYjI hbjGSjIs
(3BNQgG (B:s
(3gh eYfi dG jhLO aj GdNGQL agPg eGFI YGed dG jSJZfj GdUZjQ hGdeHjQ hGdQajY hGdhVjY Yf eYQaJgG hGSJYeGdgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 48s
(3eYLe GdeDdajf(B: 2 / 201s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs